If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x-3x=(8-x)x
We move all terms to the left:
8x-3x-((8-x)x)=0
We add all the numbers together, and all the variables
8x-3x-((-1x+8)x)=0
We add all the numbers together, and all the variables
5x-((-1x+8)x)=0
We calculate terms in parentheses: -((-1x+8)x), so:We get rid of parentheses
(-1x+8)x
We multiply parentheses
-1x^2+8x
Back to the equation:
-(-1x^2+8x)
1x^2-8x+5x=0
We add all the numbers together, and all the variables
x^2-3x=0
a = 1; b = -3; c = 0;
Δ = b2-4ac
Δ = -32-4·1·0
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{9}=3$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-3}{2*1}=\frac{0}{2} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+3}{2*1}=\frac{6}{2} =3 $
| 3x+4/2(-5x–2)–10=0 | | 8x+6=-7+2x+25 | | p(p+9)=11p+99 | | 4000=0.4x | | -(40(3d-5))=0 | | 10(n+1)=10(n)+10(1) | | -182=-4m-5(3m+6) | | 4=4/5(3d-5) | | 48–(18–58x)=28–(17+18x–57) | | 3x(2x+7)=6x^2+14x–7 | | 5(2q+6)=26 | | 3x(2x+7)=6x2+14x–7 | | -13-5x=6(2-5x) | | X^3-15x^2+75x-133=0 | | -5(7x+3)=-35x+15 | | 63x+(13–17x)–6x=63 | | 3(x=1)=1=2x=2(2x+2)+x | | 3(a-4)=6a-(3a+120 | | 46–42x=36–45x+10 | | 10(n+1)=10()+10(1) | | 2x3^2x+1+3^x-1=0 | | k+.9=1.5 | | -2(5+x)=-8 | | 10(n+1)=10() | | -6(-6-4u)=2(15u-12) | | 4-2(z-4)/3=1/2(2z+5)) | | 19n=7 | | 4g-2/5(5g-10)=10 | | 5(8+2x)=3(3x-5) | | 147−14x=78+9x | | n^2-7n=-52 | | 69-23x=0 |